Pengaruh Islamic Branding, Kualitas Produk, Dan Halal Lifestyle Terhadap Keputusan Konsumen Membeli Busana Muslimah Merek Nadheera Luxury Di Kabupaten Jepara - Anjar Wulan Sari; Edi Susilo (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2023)
The purpose of this study was to find out whether there is an influence between Islamic branding, product quality, and Halal lifestyle variables on the purchasing decision of Muslim clothing for the Nadheera Luxury brand in Jepara Regency. This research is a quantitative study, taking samples with purposive sampling, 96 consumers were selected who had bought the luxury Muslim clothing brand Nadheera in Jepara Regency. Data analysis techniques used instrument testing, classical assumption testing, and hypothesis testing using the SPSS 25 application. The results of this study indicate that Islamic branding, product quality, and halal lifestyle variables partially or simultaneously have a positive and significant effect on purchasing decisions for Muslim clothing brands. Nadheeera Luxury in Jepara Regency.